2016
DOI: 10.3389/fpls.2016.00310
|View full text |Cite
|
Sign up to set email alerts
|

AtHD2D Gene Plays a Role in Plant Growth, Development, and Response to Abiotic Stresses in Arabidopsis thaliana

Abstract: The histone deacetylases play important roles in the regulation of gene expression and the subsequent control of a number of important biological processes, including those involved in the response to environmental stress. A specific group of histone deacetylase genes, HD2, is present in plants. In Arabidopsis, HD2s include HD2A, HD2B, HD2C, and HD2D. Previous research showed that HD2A, HD2B, and HD2C are more related in terms of expression and function, but not HD2D. In this report, we studied different aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 64 publications
0
74
0
Order By: Relevance
“…Loss-of-function HD2C is hypersensitive to salt stress (Luo et al, 2012) and plants overexpressing HD2C confer resistance to ABA and drought treatments (Sridha and Wu, 2006). Overexpression of HD2D enhances salt and cold tolerance (Han et al, 2016). We observed upregulation of many ribosome biogenesis genes and downregulation of many stress response genes in hd2b hd2c (Supplemental Data Set 4).…”
Section: Evolution Of Hd2 Proteins In Plantsmentioning
confidence: 81%
See 1 more Smart Citation
“…Loss-of-function HD2C is hypersensitive to salt stress (Luo et al, 2012) and plants overexpressing HD2C confer resistance to ABA and drought treatments (Sridha and Wu, 2006). Overexpression of HD2D enhances salt and cold tolerance (Han et al, 2016). We observed upregulation of many ribosome biogenesis genes and downregulation of many stress response genes in hd2b hd2c (Supplemental Data Set 4).…”
Section: Evolution Of Hd2 Proteins In Plantsmentioning
confidence: 81%
“…It is possible that HD2 proteins may have evolved to play important roles in the environmental adaption. Genetic studies showed that HD2 proteins are involved in various stress responses (Luo et al, 2012;Buszewicz et al, 2016;Han et al, 2016). Loss-of-function HD2C is hypersensitive to salt stress (Luo et al, 2012) and plants overexpressing HD2C confer resistance to ABA and drought treatments (Sridha and Wu, 2006).…”
Section: Evolution Of Hd2 Proteins In Plantsmentioning
confidence: 99%
“…Overexpression of Arabidopsis Histone Deacetylase 2D (HD2D) resulted in a slow increase in malondialdehyde (MDA) content upon cold stress treatment. As a result, the transgenic plants were more tolerant to cold treatment (Han et al 2016). It has been shown that histone acetylation is induced upon cold treatment in the promoter regions of some COR genes, such as COR15A and COR47 (Pavangadkar et al 2010).…”
Section: Epigenetic Regulation During the Extreme‐temperature Stress mentioning
confidence: 99%
“…Similar to kinases and phosphatases involved in protein phosphorylation, protein acetylation is catalyzed by two families: the lysine acetyltransferases (KATs) and the lysine deacetylases (KDACs), which catalyze the addition and removal of acetyl groups from target proteins, respectively (Pandey et al, 2002;Tran et al, 2012b;Uhrig et al, 2017). Both protein phosphorylation and acetylation have been shown to regulate key cellular processes, such as glycolysis, nitrogen metabolism, photosynthesis (Finkemeier et al, 2011;Engelsberger and Schulze, 2012;Menz et al, 2016) and development (Han et al, 2016;Zhao et al, 2017). To date, protein phosphorylation and acetylation have each been characterized separately in plants, even though they may work synergistically or antagonistically to impact function when occuring on the same protein (Soufi et al, 2012;Tran et al, 2012a;Mertins et al, 2013;Rao et al, 2014;Sharma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%